EVALUASI PENYELENGGARAAN SISTEM UJIAN ONLINE DI UPBJJ-UT SURABAYA - Iriani, Dwi (LPPM Universitas Terbuka, 2010)
Online examination started in UPBJJ-UT Surabaya since 2005.2 named UBK (Ujian Berbasis Komputer/Computer Based Examination) until 2009.2. On 2010.1, UBK was implemented more perfectly, and the name has changed to beOnline Examination System ( Sistem Ujian Online/ SUO).However, the number of students who participated in both UBK and SUO is always less than 20 people or less than 2% of total of students of Non-Basic Education Study Program at UPBJJ-UT Surabaya. This article explains about the evaluation of the implementation of online examination, specifically on Non-Basic Education Study Program at UPBJJ-UT Surabaya. One hundred twenty five students and five administrator acted as the informant of the evaluation, and survey, in-depth interview, and direct observation were used to collect data and information. Research result showed that majority of students still do not know about online examination system and socialization of online examination system by institution was the biggest factor that affect this condition.